2001
DOI: 10.1519/1533-4287(2001)015<0178:teocso>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Creatine Supplementation on Exercise-Induced Muscle Damage

Abstract: This investigation evaluated the effects of oral creatine (Cr) supplementation on markers of exercise-induced muscle damage following high-force eccentric exercise in subjects randomly administered Cr or placebo (P) in a double-blind fashion. When injected, exogenous phosphocreatine has been shown to stabilize the muscle membrane in cardiac tissue and enhance recovery of strength and power following injury. Twenty-three men aged 18-36 years ingested either 20 g of Cr or P for 5 days. Criterion measures were ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
2
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 30 publications
7
44
2
1
Order By: Relevance
“…Prolonged creatine supplementation and repeated exercise were associated with increased CK-MM mRNA expression in one study, 18 but no effect on CK levels was observed in another. 19 It is unlikely that the single creatine dose had any effect on CK levels in Subject 18.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged creatine supplementation and repeated exercise were associated with increased CK-MM mRNA expression in one study, 18 but no effect on CK levels was observed in another. 19 It is unlikely that the single creatine dose had any effect on CK levels in Subject 18.…”
Section: Discussionmentioning
confidence: 99%
“…Woo et al 3 relataram que a administração intravenosa de PCr previne a disfunção isquêmica ventricular em ratos, indicando melhora na integridade de membranas de células cardíacas. Rawson et al 51 sugeriram que a Cr pode atenuar danos oxidativos induzidos pelo exercício em cé-lulas musculares pela manutenção da homeostase energética mitocondrial. Autores sugerem que esses mecanismos estão ligados à redução da formação de EROs e podem ser indicativos de que a Cr detém efeitos antioxidantes indiretos 5 .…”
Section: 3-propriedade Antioxidante Da Creatinaunclassified
“…12,17,49,52,53 Cr supplementation generally has not been associated with improvements in endurance exercise performance, 16,29,52 or a reduction in muscle damage with high-intensity exercise. 44 Some of the discrepancies between study results may be attributable to differences in study design, including the sex, age, and training status of the subjects (untrained individuals versus elite athletes), the sport for which athletes were trained, Cr dose and duration of supplementation (3 days-12 weeks), and the exercise tests used to assess benefits. Furthermore, while many individuals derive benefit from Cr supplementation, others appear to be nonresponders, which may be explained by the variability in skeletal muscle accumulation of Cr with supplementation.…”
Section: Effects Of Creatine Supplementation On Performancementioning
confidence: 99%